Enslaved Phase-Separation Fronts and Liesegang Pattern Formation (Communications in Computational Physics, 2020)
We show that an enslaved phase-separation front moving with diffusivespeeds  can leave alternating domains of increasing size in their wake. Wefind the size and spacing of these domains is identical to Liesegang patterns. For equalcomposition of the components we are able to predict the exact form of the pattern analytically.To our knowledge this is the first fully analytical derivation of the Lieseganglaws. We also show that there is a critical value for C below which only two domainsare formed. Our analytical predictions are verified by numerical simulations using alattice Boltzmann method.